Were There “Additional Foreseeable Risks” in the SUPPORT Study? Lessons Not Learned from the ARDSnet Clinical Trials - Silverman, Henry J. (The Hastings Center report, 2015)
SUPPORT, a study involving approximately 1,300 premature infants who were randomly assigned to treatment protocols that differed in whether they offered higher or lower levels of oxygen saturation, was purportedly an example of comparative effectiveness research performed in the intensive care unit. However, SUPPORT became highly controversial. One source of controversy involved the proper determination of “reasonably foreseeable risks.” Commentators debated whether randomization to contrasting restrictive strategies that are within existing standard-of-care treatments imposed additional “reasonably foreseeable risks” greater than what study participants would have received outside of the research. A second controversial issue had to do with disclosures in informed consent documents. This article explores these issues. We argue that randomization to contrasting restrictive interventions lying at the outer ends of “standard-of-care” practices differs in important ways from unrestricted “standard-of-care” practices available outside of a proposed study; that research involving such randomization might pose additional “reasonably foreseeable risks” from what occurs in “standard-of-care” practices; and that for trials whose study designs are similar to the SUPPORT study, respect for persons requires the disclosure of information about the nature of the experimental procedures and their risks.